DOES PROCEDURAL JUSTICE AND DISTRIBUTIVE JUSTICE MEDIATE THE EFFECT OF JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT?: CASE STUDY OF EDUCATION INSTITUTION - Bagis, Fatmah; Ilma Hartikasari, Annisa; Cinintya Pratama, Bima (Derivatif : Jurnal Manajemen, 2018)
This study investigates job satisfaction and its effects on organizational commitment, where procedural justice and distributive justice are used as mediation variables. The method used in this study is a case study on employees of educational institutions in Purwokerto. Questionnaires were given to 74 employees from the management level to the staff level as respondents. Data analysis technique used is the analysis of PLS (Partial Least Square) using SmartPLS 3.0. The results showed that Job Satisfaction has a significant effect on Procedural Justice and Distributive Justice, Procedural Justice has no significant effect on Commitment of Oganization, while Distributive Justice has a significant effect on Organizational Commitment. It also proves that distributive justice mediates the relationship between job satisfaction and organizational commitment, but procedural justice can not mediate the relationship between job satisfaction and organizational commitment.Â Keywords: distributive justice, job satisfaction, organizational commitment, procedural justice.